OVERCOMING SMALL HOLDER FARMERS’ FINANCIAL EXCLUSION USING ANCHOR BORROWERS’ PROGRAMME IN YOLA NORTH AND YOLA SOUTH LOCAL GOVERNMENT AREAS, ADAMAWA STATE, NIGERIA - Dengle Yuniyus GIROH; Abubakar Ahmadu TAFIDA; Linus MORRIS; Grace Kulipanani MARCUS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Rural areas in Nigeria are the centres of agriculture-based economic activity and fuel the livelihoods of 70% and contribute over 22.30% of the country’s Gross Domestic Product (GDP). It is estimated that Nigerian agricultural output would increase if farmers were able to access the finance they need to expand both the quality and quantity of their produce. The limited level of Agricultural credit is considered an important factor for increased agricultural production and food security because, it enhances productivity and promotes standard of living by breaking the vicious cycle of poverty of small scale farmers. The study was conducted on Overcoming Small holder Farmers’ Financial Exclusion using Anchor Borrowers’ Programme in Yola North and Yola South Local Government Areas, Adamawa State, Nigeria. Data were collected using structured on 94 farmers randomly selected. Descriptive and inferential statistics were used in the analysis of the data collected. Descriptive analysis revealed that respondents were relatively young with a mean age of 40 years, a mean family size of 6 people who are mostly small holder farmers with the mean farm size of 3.21 hectares and are experienced with a mean experience of 10 years. Logit result with Diagnostic statistics and VIF test results indicated that the Hosmer and Lemeshow goodness of fit test indicating that our model fits the data well. The model also correctly predicted 73.68 % of the dependent variables. The estimated VIF suggested that the explanatory variables specified in the model do not cluster together or exhibit multicollinearity tendencies. This implies that the estimates of the model to an appreciable extent are consistent and unbiased, stable over time and there was also no problem of multicollinearity. Furthermore, the result showed that membership of cooperative society, age, primary occupation, income and training were statistically significant and increases the probability of access to agricultural credit. Government policies that would encourage young people to go into agriculture should be sustained by the government at all levels in areas of credit supply, training and supply of basic production inputs to boost production, increase food security and reduction in poverty. Farmers should be encouraged to form cooperative societies to maximize the economics of scale.